Factors Affecting Teachers’ Perception of Principal Leadership Behavior in International Schools of Thailand - Ye, Yan (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
Given the increasing diversity and competitiveness of international schools, understanding how leadership behaviors influence teachers’ professional well-being is essential. The study aimed: (1) to identify the current level of principal leadership behavior as perceived by teachers; (2) to examine the effects of teachers’ demographic characteristics on these perceptions; and (3) to analyze the relationships and direct and indirect effects among principal leadership behavior, school climate, teacher self-efficacy, and job satisfaction. Data were collected from 535 full-time teachers working in four large international schools representing American, British, International Baccalaureate, and other national curricula through purposive sampling method. The findings revealed that teachers perceived principal leadership behavior, school climate, self-efficacy, and job satisfaction at high levels. Nationality and years of teaching experience significantly influenced teachers’ perceptions of principal leadership behavior, while gender, age, and educational background showed no significant differences. Correlation and path analyses demonstrated that principal leadership behavior had significant direct effects on teacher self-efficacy and job satisfaction. Furthermore, school climate partially mediated the relationships between leadership behavior and both teacher outcomes. The proposed model explained substantial variance in teacher self-efficacy and job satisfaction. This study contributes an integrated leadership–climate–outcome framework applicable to multicultural international school contexts. The findings highlight the importance of relational, instructional, and participatory leadership practices in fostering supportive school climates and enhancing teachers’ professional well-being. The results provide practical implications for leadership development and school improvement strategies in international education settings.